Prevalence and Risk Factors of Dry Eye Disease in Kuantan, Malaysia - Aljarousha, Mohammed; Abd Rahman, Aziimah A; Badarudin, Noor E; Che Azemin, Mohd Z; Awad, Khalid (Makara Journal of Health Research, 2018)
Background: To determine the prevalence of dry eye disease (DED) at Jalan Hospital Eye Care, International Islamic University Malaysia (IIUM), Kuantan, Malaysia. Methods: The dry eye symptoms and tear breakup time test (TBUT) values retrieved from the medical records of 643 patients were retrospectively analysed. Dry eye cases with one or more symptom were included. ‘Yes’ or ‘no’ responses were used in discriminant analysis of tear abnormality (TBUT < 5 seconds). Results: The crude prevalence of DED was 48.5%, the age-adjusted prevalence was 43% in women <50 years of age, and 68.4% in those ≥50 years of age. Contact lens wear and low TBUT values were associated with DED risk in men. Age of ≥50 years and a low tear meniscus height (TMH) score were associated with risk of DED symptoms in women. Conclusions: The prevalence of DED in optometric outpatients at IIUM was relatively high, especially in the elderly population. Symptoms and signs were poorly associated with DED. TBUT performed well in diagnosing dry eye and may be useful to improve the assessment of patients with dry eye problems in this region.